Does Classical Competition Explain the Statistical Features of Firm Growth? - Simone Alfarano; Mishael Milaković (Kiel University, Department of Economics, 2008)
We express the idea of classical competition in a statistical equilibrium model, where the tendency for competition to equalize profit rates results in an exponential power (or Subbotin) distribution. The model supports and extends recent evidence on the Laplace distribution of growth rates in firm size. We also find tent-shaped distributions in the size growth rates of Forbes Global 2000 companies, which we interpret as preliminary evidence in favor of the hypothesis that classical competition is a globally operating mechanism.
Keywords: F01; E10; D21; L10; C16; 330; Statistical equilibrium; classical competition; maximum entropy; profit rates; firm growth rates; Subbotin distribution; Laplace distribution; Wettbewerb; Unternehmenswachstum; Betriebsgrößenstruktur; Statistische Verteilung; Theorie; Welt